AM Design of E-Budget with SAP Integration Using the Design Thinking Method for Budget Management Optimization at PT. Krakatau Steel - Megayanti, Anita; Ritonga, Roy Amrullah; Gustina; Hendriyati, Penny (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
Integrated budget management is a crucial aspect of enhancing efficiency and accuracy in corporate budget planning and realization. One of the innovations developed to address this need is the E-Budget system, an application designed to automate the processes of budget submission, evaluation, implementation, and monitoring in a more systematic manner. However, the implementation of this system still faces several challenges, such as a time-consuming and error-prone budget data input process, lack of integration with the SAP system, which hampers data processing, and limited access that is only available through the intranet network. Additionally, the lack of transparency in the budget evaluation process also hinders data-driven and more accurate decision-making. To overcome these challenges, the Design Thinking approach is applied in the development of the E-Budget system to better align with user needs. This method enables the design of a more intuitive, flexible, and easily accessible system, thereby improving efficiency in budget management. This study aims to design an E-Budget system integrated with SAP using the Design Thinking method to optimize data collection and enhance user accessibility. The expected outcome of this system development is to simplify the budget data input process at PT. Krakatau Steel, improve the effectiveness of budget planning and supervision, and accelerate real-time data access. With a more transparent and efficient system, the company is expected to optimize financial management.